2012
DOI: 10.1063/1.4730959
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of terahertz gyrotron based systems for remote detection of concealed radioactive materials

Abstract: This paper analyzes some features of systems intended to remotely detect concealed radioactive materials by using a focused THz radiation. This concept is based on possibility to focus high-power THz radiation in a small spot where the wave field exceeds the breakdown threshold. However, in the absence of any sources of ionization, the probability to have in this breakdown-prone volume any seed electrons is very low. Thus, high breakdown rate in a series of THz pulses will indicate the presence of concealed ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The temporal evolution of plasma in such breakdowns will be analyzed in the subsequent work. Possible benefits from using pulse compressors, which shorten the pulse duration but increase the wave power and, hence, the breakdown-prone volume, were analyzed [10]. It is shown that the use of pulse compressors can significantly improve the sensitivity of the system.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal evolution of plasma in such breakdowns will be analyzed in the subsequent work. Possible benefits from using pulse compressors, which shorten the pulse duration but increase the wave power and, hence, the breakdown-prone volume, were analyzed [10]. It is shown that the use of pulse compressors can significantly improve the sensitivity of the system.…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2). In previous studies [2,3] it was shown that at a higher frequency the discharge evolution is associated with continuous propagation of the ionization front, whereas at a lower frequency this evolution is associated with quasi-periodic jumps of the ionization front. The continuous propagation of the ionization front is accompanied by smooth evolution of the reflection coefficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The breakdown delay time, as well as the plasma parameters, is sensitive to existence of radioactive materials which can ionize air producing thereby seed electrons in the vicinity of the breakdown prone volume [1][2][3]. Therefore a study of the breakdown evolution can give some particular information about the closeness of radioactive materials to the focal spot of high power microwave beam [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding conditions were analyzed elsewhere. [16][17][18] In particular, it was shown that an attractive option would be a 670 GHz gyrotron delivering the power above 200 kW in 10-20 ms long pulses. The choice of the frequency was determined by two factors.…”
mentioning
confidence: 99%